Sino-African relations in West Africa: implication for ecowas / Ibrahim Ishola Yahaya and Abdul Rauf Ambali - Yahaya, Ibrahim Ishola; Ambali, Abdul Rauf (Universiti Teknologi MARA, 2021)
Chinese relations with Africa began as early as the Christian era. However, modern China’s involvement in the continent dates back to the Bandung Conference of April 1956 where China and representatives of 29 African countries agreed on certain terms of engagements. However, the rivalry between the defunct Soviet Union and China enhanced the presence of China in Africa. These relations suffered a setback with the death of the China’s leader, Mao Zedong.Deng Xiaoping who succeeded him paid more attention to the economic development of China. Consequently, he shifted foreign policy attention of China towards forging ties with global economic powers and institutions. Thus, Sino-African relations remain docile between 1970 and 1980s. The improved economic fortune of China in the 1990s coupled with the end of cold war era, made China to renew her engagement in the continent not only as source of raw materials for her new industries, but as source of market. While this renewed engagement of China has been controversial, all African countries currently enjoy robust relations with China in various forms. This work examines these relationships with a view to assessing their implications for economic integration in the West African sub-region Vis-a- Vis the objectives of Economic Community of West African States (ECOWAS). We use secondary source of data as research method. The paper finds that Sino-Africa relations have potentials for positive impact on each country in the sub-region if properly handled by the West African countries. It could in the long run add positively to economic integration of the sub-region.